Estimación del potencial de captura de carbono, de la especie capirona (caycophyllum spruceanum) en el centro ecológico la Julianita - Rodriguez Celiz, Sergio (2014)
This research study was carried out in the Julianita Ecological Center, Moyobamba district, Moyobamba province, San Martín department. Had as its main objective: To estímate the carbon sequestration potential of the Capirona species (Calycophyllum spruceanum) in the Julianita Ecological Center, andas specific objectives: a) Determine the carbon captured in the biomass ofliving trees. b) Determine the carbon captured in the biomass of litter. e) Determine the influence of the carbon sequestration potential in the Julianita Ecological Center. The experimental design was used experimental blocks at random, with 7 replicates, carried out every 15 days eaming a total of 28 samples. Were made the data collection for the deterrnination of biomass in the Capirona planting, the sample drying was carried out at ambient temperature are the sample weight every 3 days until, obtain a uniform weight of the sample; with information obtained from the work of cabinet the following results were obtained: • The influence of the carbon sequestration potential in the Julianita Ecological Center is important because it was deterrnined that the species Capirona (Calycophyllum sprucearum), captured 9.94 tnlha of carbon and is a major carbon sink due to the plantation can be harvested from the fifth year of sowing and can reach maturity to the tenth year. • Carbon captured in the biomass of trees of the Capirona species live (Calycophyllum sprucearum) in the Julianita Ecological Center was 1.79 tnlhas captured carbon. • Carbon captured in the biomass of leaf litter of the Capirona (Calycophyllum sprucearum) species in the Julianita Ecological Center Was 14.93 Tnlhas captured carbon. • The methodology applied proved to be viable and not gender many expenses, use the DBH (diameter at breast height) as the only independent variable simplifies the work of field and allows you to estímate the carbon captured without the need for studies in laboratory, which are expensive and difficult to access in our country. Key words: Capirona species; carbon sequestration.